(untitled) (Al-Academy, 2018)
The research tackles an important subject, namely, the light text and how it works well in the Arab television programs. The methodological framework of the research presents the research problem stated in the following question: How can the text be used and what is its impact in the Arab TV programs? The importance of this research is that it deals with the subject of light text and its impact on Arab television programs. This study is useful to the workers and scholars in the field of lighting as well as the goal of the research in (studying of the employment of light text in Arab television programs). The limits of research were manifested in the study of the light text and how to make use of it in Arab television programs, including an analysis of the sample which is "The Voices" produced in 2012. The theoretical framework was divided into two main sections the first was entitled (light: concept and work) in which the researcher discussed the most important scientific and philosophical theories that dealt with this subject in addition to the types of lighting and how to make use of them. The second topic was entitled (the interactive programs). The researcher pointed out the importance of these programs and how to implement them especially lighting which plays a major role in the construction of these programs. The researcher, after discussing these two sections, came up with a number of theoretical framework indicators that were submitted to a number of experts and arbitrators in order to make them resemble a unit of measurement for the implementation of the analysis. The researcher, in the research procedures, clarified his choice of the descriptive method in the analysis of the sample being the closest to the field of his specialization in addition to the analysis tool that was referred to and then the unit of analysis, which was summarized by the screenshot as a basic unit in the analysis of the sample (The Voice). The researcher came up with a number of results, conclusions, recommendations and proposals and then concluded his research with a list of sources and references